The Empowerment of American Women during the Great Depression in Comparative Perspective - Arroyo Vázquez, Maria Luz (Review of International American Studies, 2015)
Maria Luz Arroyo Vázquez Universidad Nacional de Educación a Distancia, Spain This paper examines the significant progress that women made during the Great Depression and will focus its attention on the Roosevelt era, a period in which women not only reached key posts in the administration but also managed to acquire a new dignity and social status. Besides, it will try to explore the echo that some of these significant women had across other countries, giving as an example the Spanish case. Roosevelt’s four terms in office (1933–1945) were a clear example of a time when women participated actively in public life. Women were appointed to relevant government positions and played key roles in the development of the Roosevelt Administration. Roosevelt himself and his federal government fostered these expanded roles for women who worked as heads of Federal agencies, as political advisers, in the New Deal’s relief programs, etc. Behind these appointments, we have to highlight the support and compromise of relevant women such as Eleanor Roosevelt, Frances Perkins, Mary Bethune and Molly Dewson, just to mention some of the most inspiring figures during this era. Women worked in two main areas: Democratic Party politics and social welfare. As Susan Ware points out, there was “a network of professional contact and personal friendship that linked the women in top New Deal positions”. In summary, this paper tries to acknowledge and pay tribute to those women, who proved their talent and self-worth and to the ones who were deeply committed with the defence of social reforms and participated actively in politics and social welfare legislation during the Roosevelt era.